The development of online narrative in video games: The player’s agency in Grand Theft Auto V Roleplay - Martínez , Kim (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Grand Theft Auto (GTA) V Roleplay is a mode of its online multiplayer version that transforms the narrative, interaction, and original mechanics. Five server types (Drift, Race, Players Versus Players, Players Versus Environment and Roleplay) are studied to determine what possibilities each offers and what kind of agency the player achieves. Each category builds a different experience by implementing narrative events, factions, or social interactions. Thus, it is determined that, although GTA Roleplay became popular thanks to influencers, it continues to develop thanks to the engagement of its players.